Pembimbingan Dan Evaluasi Pada Kegiatan PLP Di SMK Muhammadiyah 1 Pekanbaru - Shilvi Dwita; Rahmad Al Rian (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The introduction of the school field (PLP) activity was carried out as an effort to form qualified prospective educators students of The Bachelor of Education Study Program are required to take PLP courses. Through PLP, students are expected to improve their pedagogy, social personality and professional skills. This article discusses the implementation of the introduction of the school field (PLP). The results of the introduction of field schooling (PLP) are described using qualitative descriptive methods. Dinalisa evaluation based on the assessment of the Mentoring Teacher. Based on the evaluation results, PLP participant students of Muhammadiyah University of Riau who PLP in SMK Muhammadiyah 1 Pekanbaru have successfully met the indicators that have been set in the implementation of PLP activities.